Parents as Partners: A U.K. Trial of a U.S. Couples‐Based Parenting Intervention For At‐Risk Low‐Income Families. Issue 3 (24th April 2017) - Casey, Polly; Cowan, Philip A.; Cowan, Carolyn P.; Draper, Lucy; Mwamba, Naomi; Hewison, David
Abstract : Despite the well‐established links between couple relationship quality and healthy family functioning, and burgeoning evidence from the international intervention field, there is little or no evidence of the efficacy of couples‐based interventions from the United Kingdom (U.K.). This study explored whether the Parents as Partners (PasP) program, a group‐based intervention developed in the United States, brought about the same benefits in the U.K. The evaluation is based on 97 couples with children from communities with high levels of need, recruited to PasP because they are at high risk for parent and child psychopathology. Both mothers and fathers completed self‐report questionnaires assessing parents' psychological distress, parenting stress, couple relationship quality and conflict, fathers' involvement in child care and, importantly, children's adjustment. Multilevel modeling analysis comparing parents' responses pre‐ and postintervention not only showed substantial improvements for both parents on multiple measures of couple relationship quality, but also improvements in parent and child psychopathology. Analyses also indicated most substantial benefits for couples displaying poorest functioning at baseline. The findings provide initial evidence for the successful implementation of PasP, an American‐origin program, in the U.K., and add support for the concept of the couple relationship as a resource by which to strengthen families. Abstract : Video Abstract